Identification of botanicals with potential therapeutic use against methicillin‐resistant Staphylococcus aureus (MRSA) infections. (25th September 2018) - Gerstel, Johanne; Turner, Tiffany; Ruiz, Guillermo; Wise, Justin; Stein, Ashley; Jones, Greg; Morin, Tanya; Pinazza, Tony; Sukhorukov, Elena; Clark, Donna; Steen, Taelor; Wright, Berlin; et al.
Abstract : Staphylococcus aureus is an opportunistic pathogen. Over‐ and improper‐use of pharmaceuticals against S .  aureus has led to the development of antibiotic resistance, including methicillin‐resistant S. aureus (MRSA). This study examined the efficacy of botanical extracts as an alternative form of treatment to S. aureus and MRSA, including penicillin/methicillin‐resistant S. aureus (Pen R ), and multidrug resistant S. aureus (MDR). Initial screening of botanicals was done via a minimum inhibitory concentration procedure. In addition, a temporal growth curve was performed in order to quantify the growth of the bacteria in the presence of the extracts. Results demonstrated 13 botanicals that had varying activities against S. aureus, Pen R, and MDR. These botanicals were separated into mild, moderate, and highly efficacious based on the concentration needed to inhibit bacterial growth. These results propose a comparison of botanical‐derived antimicrobial extracts that may be utilized against S. aureus and different antibiotic resistant strains of MRSA.